Commercial sex work among university students: a case study of four public universities in Ghana - Fred Yao Gbagbo; Josephine Akosua Gbagbo (BMC, 2021)
Abstract Background Despite its criminalization in Ghana, commercial sex work dates back to ancient societies and occurs in various forms within communities. The authors examined commercial sex work in selected public Universities in Ghana to inform policy and program decisions for safer sex at the universities in Ghana. Methods The study was an exploratory-mixed-method design. Respondents were identified using purposive and snowballing techniques while semi-structured questionnaires and in-depth interviews were used for data collection between 2017and 2019. Quantitative data were analyzed using Statistical Package for Social Sciences version 23 and qualitative data analyzed thematically. Results Findings show that there is a proliferation of commercial sex work on university campuses in Ghana for financial, material, and emotional gains. Student sex workers have devised various strategies to combine academic work and sex work. Prospective customers are solicited by hanging out in drinking bars and nightclubs in and around university campuses at night and/or leaving contact details with pimps to be contacted for services. Brothels are also springing up in and around the university campuses in the form of movie houses and student sex workers convert their hostel rooms into brothels. Price negotiation is based on the environment, duration, the sex workers' perceived safety of the sexual act, customer's preferences for styles, and positions adopted for sex. Conclusion There is a need for further studies in this area and a multi-sectoral approach for appropriate policy and program interventions to regulate the practice on campus.